(untitled) (Chichester, 2007)
The book is a focus on the algorithmic and computational augmentations of fuzzy clustering and its effectiveness in handling high dimensional problems, distributed problem solving and uncertainty management; presentations of the important and relevant phases of cluster design, including the role of information granules, fuzzy sets in the realization of human-centricity facet of data analysis, as well as system modelling; demonstrations of how the results facilitate further detailed development of models, and enhance interpretation aspects; a carefully organized illustrative series of applications and case studies in which fuzzy clustering plays a pivotal role
Keywords: Fuzzy systems,Soft computing,Hệ thống mờ,Trí tuệ nhân tạo